The effects of hip angle on foot placement while running - Hesener, A.; Howard, D.; Jin, J.
In our study we were interested in finding out if differences in the hip angles of males and females affected the amount of crossover exhibited in the running motion. While the male and female subjects differed in other kinematic variables of their gait patterns, the amount of crossover was the same. Both subjects moved their base of support (i.e. the foot) underneath their center of mass. Since the center of mass for both subjects had the same horizontal position, the amount of crossover was related to this value and not to hip angle. However, because of her larger hip angle, the female subject needed to undergo a larger degree of angular displacement at the hip and a larger degree of pelvic tilt than the male subject. She also had to accelerate her leg to a greater angular velocity to accomplish a larger amount of displacement in the same amount of time. Basically, there were differences in the running motion of the two subjects, but these differences ultimately resulted in a nearly identical outcome in terms of foot placement. Despite our findings on the similarity of the crossover in two runners with different hip angles, the fact that other kinematic properties of the gait cycles do differ with hip angle to accomplish the same amount of crossover may be significant. Gender differences in running economy have been found (Anderson, 1996; Morgan 1989), and the possibility exists that females exhibit less running economy may in fact be due to the fact that a runner with a larger hip angle has to achieve more displacement and acceleration of the limb in order to produce a running motion that centers the base of support under the center of mass. This is necessary to the running motion to avoid placing too much of the load of the body weight on the hip adductors (Cavanagh 1987). Just because our subjects had the same amount of crossover does not mean that this is true for the general population. The fact that we only had two subjects in our study is a major limitation of our study. We generalized our results to all males and females based on the results we obtained with one representative of each gender. These are not valid generalizations and more research must be done to form the conclusions stated here. Also, we only analyzed one gait cycle for each subject. There may be considerable differences within individuals as to the amount of crossover they exhibit with each step (Cavanagh 1987). Different runners do in fact show different bases of gait (the amount of crossover) that range from positive to negative (Cavanagh 1987) so in a larger study we would expect to find more variances that may change the results. In addition, our methods may have limited us in that the differences we were looking for may have been too small to show up in our analysis using digitization and the subjects may have slightly altered their running motion since they were running on a treadmill rather than over ground.